Pembrolizumab for previously treated, microsatellite instability-high/mismatch repair-deficient advanced colorectal cancer: final analysis of KEYNOTE-164 - Le, Dung T.; Diaz, Luis A.; Kim, Tae Won; Van Cutsem, Eric; Geva, Ravit; Jäger, Dirk; Hara, Hiroki; Burge, Matthew; O’Neil, Bert H.; Kavan, Petr; Yoshino, Takayuki; Guimbaud, Rosine; et al. (European journal of cancer, 2023)
Background - Pembrolizumab demonstrated durable clinical benefit and manageable safety in previously treated advanced or metastatic microsatellite instability-high (MSI-H)/mismatch repair deficient (dMMR) colorectal cancer (CRC) in the phase 2 KEYNOTE-164 study. Results from the final analysis are presented. - Methods - Eligible patients had unresectable or metastatic MSI-H/dMMR CRC and ≥2 prior systemic therapies (cohort A) or ≥1 prior systemic therapy (cohort B). Patients received pembrolizumab 200mg intravenously every 3 weeks for ≤35 cycles. The primary end-point was objective response rate (ORR) assessed per Response Evaluation Criteria in Solid Tumors, version 1.1 by blinded independent central review. Secondary end-points included duration of response (DOR), progression-free survival (PFS), overall survival (OS), and safety and tolerability. - Results - Sixty-one patients in cohort A and 63 patients in cohort B were enroled; median follow-up was 62.2 months and 54.4 months, respectively. ORR was 32.8% (95% CI, 21.3%-46.0%) in cohort A and 34.9% (95% CI, 23.3%-48.0%) in cohort B. Median DOR was not reached (NR) in either cohort. Median PFS was 2.3 months (95% CI, 2.1-8.1) in cohort A and 4.1 months (95% CI, 2.1-18.9) in cohort B. Median OS was 31.4 months (95% CI, 21.4-58.0) in cohort A and 47.0 months (95% CI, 19.2-NR) in cohort B. No new safety signals were observed. Nine patients who initially responded experienced disease progression off therapy and received second-course pembrolizumab. Six patients (66.7%) completed an additional 17 cycles of pembrolizumab, and 2 patients achieved a partial response. - Conclusions - Pembrolizumab continued to show durable antitumor activity, prolonged OS, and manageable safety in patients with previously treated MSI-H/dMMR CRC. - Clinical Trial Registry Information - ClinicalTrials.gov, NCT02460198